THE CONTRIBUTION OF NUTRIENT BASED ON THE MANGROVE TYPES IN PANGKALAN SESAI REGION DUMAI CITY - Novia Suci Yanti; Bintal Amin; Efriyeldi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis study was conducted in April-May 2014 in an area of mangrove forest in Pangkalan Sesai Region Dumai city. The purpose of this study was to determine the differences in litter decomposition rates of different mangrove species at several locations in Pangkalan Sesai Region and to understand the contribution of nutrients (N and P) production of mangrove litter on different type of mangrove. The method used was the method of surveying, sampling and testing of mangrove litter decomposition rates in the mangrove forest in Pangkalan Sesai Region. Nitrate and Phosphate sample analysis carried out in the Laboratory Marine Science, Faculty of Fisheries and Marine Sciences University of Riau. The highest rate of litter decomposition found in Avicennia sp at Station I which took place on the 30th day was the decomposition of 6.67 grams, with a percentage of 2.22% per day. Depreciation lowest leaves are exist at Station III is the species of Rhizophora sp 6.876gr which lost weight at 3.13 grams. Average production potential of nutrients (N and P) based on the type of mangrove in the entire station is nutrients nitrate in Avicennia sp 0.0002 g-N/m2/day, Xylocarpus sp 0.0002 g-N/m2/day, and Rhizophora sp 0.0001 g-N/m2/day. For nutrient phosphate in Avicennia sp 0.0010 g-P/m2/day, Xylocarpus sp 0.0052 g-P/m2/day, Rhizophora sp 0.0054 g-P /m2/day.Key Word: Mangrove, Litter, The rate of dekompostion, Nutrient, Pangkalan Sesai.